Cuttlefish-Bone-Derived Hybrid Composite Scaffolds for Bone Tissue Engineering - Vignesh Raj Sivaperumal; Sutha Sadhasivam; Ramalingam Manikandan; Ilanchezhiyan Pugazhendi; Saravanan Sekar; Youngmin Lee; Sejoon Lee; Sankar Sekar (Nanomaterials)
Current investigations into the fabrication of innovative biomaterials that stimulate cartilage development result from increasing interest due to emerging bone defects. In particular, the investigation of biomaterials for musculoskeletal therapies extensively depends on the development of various hydroxyapatite (HA)/sodium alginate (SA) composites. Cuttlefish bone (CFB)-derived composite scaffolds for hard tissue regeneration have been effectively illustrated in this investigation using a hydrothermal technique. In this, the HA was prepared from the CFB source without altering its biological properties. The as-developed HA nanocomposites were investigated through XRD, FTIR, SEM, and EDX analyses to confirm their structural, functional, and morphological orientation. The higher the interfacial density of the HA/SA nanocomposites, the more the hardness of the scaffold increased with the higher applied load. Furthermore, the HA/SA nanocomposite revealed a remarkable antibacterial activity against the bacterial strains such as E. coli and S. aureus through the inhibition zones measured as 18 mm and 20 mm, respectively. The results demonstrated a minor decrease in cell viability compared with the untreated culture, with an observed percentage of cell viability at 97.2% for the HA/SA nanocomposites. Hence, the proposed HA/SA scaffold would be an excellent alternative for tissue engineering applications.